Harnessing customer mindset metrics to boost consumer spending: a cross-country study on routes to economic and business growth - Shaalan, Ahmed; Agag, Gomaa; Tourky, Marwa (Wiley, 2022)
The relationship between customer mindset metrics (CMMs) and consumer spending has been extensively investigated at the consumer and firm level, but little is known about it at the national level, nor about how it differs between countries. Drawing on five publicly available datasets gathered in 10 European countries over 20 years, our study traces the connections between three CMMs – customer satisfaction, perceived service quality and loyalty intentions – and consumer spending, as well as examining the moderating cross-country effects of culture, socioeconomic factors, economic structure and political–economic elements. The results show that the CMMs significantly influence consumer spending in all the countries studied, with the effects most pronounced in societies with relatively low education levels, a dominant service sector, fewer barriers to business and international trade and a foundation of survival values rather than self-expressive values. Our findings suggest that CMMs can be used to boost not just business performance but also economic growth, and therefore have significant implications for policymakers as well as practitioners and companies.
Keywords: Customer mindset metrics; Consumer spending; Self-expressive values; Culture